1996
DOI: 10.1111/j.1348-0421.1996.tb01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Actinobacillus actinomycetemcomitans Hemolysin

Abstract: Twenty out of 33 Actinobacillus actinomycetemcomitans strains formed hemolytic colonies on horse blood agar plates under anaerobic conditions. The hemolytic activity found in A . actinomycetemcomitans strain 137HE was examined. This activity was detected in the late exponential to early stationary phases of growth. Human erythrocytes were the most susceptible, followed by rabbit, sheep, horse and swine red blood cells. The majority of activity was detected in the cell-associated vesicle fraction. Zwitterionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
24
2
Order By: Relevance
“…A likely explanation for this conclusion, which conflicts with the work that we de- (24). However, they found that their hemolysin had a molecular mass of 12 kDa, which is much less than the molecular mass of LtxA (ϳ114 kDa).…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…A likely explanation for this conclusion, which conflicts with the work that we de- (24). However, they found that their hemolysin had a molecular mass of 12 kDa, which is much less than the molecular mass of LtxA (ϳ114 kDa).…”
Section: Discussioncontrasting
confidence: 53%
“…We have also shown previously that breakdown of LtxA is common in older cultures of A. actinomycetemcomitans (19). Thus, we suggest that Kimizuka et al (24) may have indeed isolated LtxA as the hemolysin but that the 12-kDa protein represented one of leukotoxin's major breakdown products (19).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Numerous A. actinomycetemcomitans strains express cx-hemolysin activity, but the significance of this is not known (Avila-Campos, 1995). Another study, describing two distinct A. actinomycetemcomitans hemolytic activities (against human, horse, sheep, and rabbit), suggests that A. actinomycetemcomitans may possess multiple hemolysins (Kimizuka et al, 1996). Others have been unable to demonstrate A. actinomycetemcomitans' hemolytic activity toward sheep or rabbit blood cells (Slots, 1982).…”
Section: Escape From the Vacuole: Phospholipase C Activity Is A Candimentioning
confidence: 96%